Hidden geographies of social justice in an urban environment: The particularities of naturally-occurring arts districts - Peter KUMER (European Journal of Geography)
Despite extensive research on the role arts districts play in the economic development of cities, little is known about the dynamics of social interactions within those districts and their impact on society. Drawing on 26 interviews with actors and stakeholders of arts districts in Ljubljana, this paper explores the role of arts districts in creating a just city. Four dimensions of such districts, which represent the meaningful themes that emerged from the data, are examined. The first dimension is the interrelationship of artists, cultural workers and activists. The second dimension encompasses mutual support and forms of self-governance, whereas the third dimension investigates the role arts districts play in the neighbourhood. The fourth dimension seeks to define the role of arts districts as part of urban development generally driven by capital.The results show that arts districtsare important in the struggle for the right to the city. Actors from these districts are committed to addressing the causes of social inequality at their root via artist-led civic engagement activities